Effect of oral and intravenous hydration therapy on amniotic fluid index, maternal and perinatal outcome in borderline oligohydramnios - Chaudhary, Anjali; Varma, Umesh; Goel, Sandeep; Tayal, Ankita; Varma, Aditya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The aim was to determine whether oral route of maternal hydration was advantageous over intravenous route in terms of increasing AFI and improving maternal and perinatal outcome in women having borderline oligohydramnios. Methods: At Aarogya hospital, 150 women in third trimester with borderline oligohydramnios (BO) AFI 5.1-8 cm, were divided randomly into two groups, oral hydration group (OG) and intravenous hydration (IVG). Each case was studied on OPD basis. After 2 hours, 48 hours and 1 week of oral or IV hydration. AFI was reassessed by same sonographer. Pre-delivery AFI and various outcome measures were recorded for both groups. Results: There was an increase in AFI by 44.5% in OG from 0 hour till delivery as compared to 30.7% increase in IVG. MSL occurred in 8 (10.7%) women in OG compared to 17 (22.6%) in IVG. FD was found in 4 (5.3%) in OG requiring LSCS compared to 16 (21.3%) in IVG. Total of 59 (78.7%) patients in OG has spontaneous vaginal delivery as compared to 42 (56%) in IVG. Perinatal outcome was better with OG than IVG 67 (89%) had Apgar at 1 min >8 in OG than 58 (77%) in IVG. Apgar score <8 at 1 min was seen in 8 (10.7%) in OG while 17 (22.7 %) in IVG. Overall, 7 (9.3%) required NICU admission in OG and 12 (16%) in IVG. Conclusions: AFI increment persisted longer in OG as compared to IVG. Maternal and perinatal outcome were better with oral hydration therapy than IV hydration.